Genetic Variation in Taste Receptor Genes (SCNN1B, TRPV1) and Its Correlation with the Perception of Saltiness in Normotensive and Hypertensive Adults. (4th June 2021) - Tapanee, Pradtana; Tidwell, Diane K.; Schilling, M. Wes; Peterson, Daniel G.; Tolar-Peterson, Terezie
Abstract : Background . Different taste preferences correlated with genetic variations may lead to food consumption patterns that contribute to nutrient-related health outcomes such as hypertension. Objectives . The aim of this study was to determine whether single nucleotide polymorphisms (SNPs) in the salt taste receptor genes SCNN 1 B and TRPV 1 affect salt taste perception among normotensive and hypertensive people. Materials and Methods . We conducted a cross-sectional case control study by design consisting of a normotensive and hypertensive group. Participants were 253 adults with age range of 20–82 residing in Mississippi, USA. For each of 128 normotensives and 125 hypertensives, the salt taste recognition threshold and salt taste receptor genotype were determined. Results . The hypertensive group had a higher salt taste recognition threshold than the normotensive group (P < 0.001 ). The polymorphism of TRPV 1, rs4790522, with the AA genotype was associated with a higher salt recognition threshold (lower salt taste sensitivity) in people with hypertension and obesity. Moreover, the polymorphism of TRPV 1, rs8065080, and SCNN 1 B, rs239345, genes were associated with a risk of hypertension (P = 0.016 and P = 0.024 ). Conclusion . Correlations between SNPs, salt taste sensitivity, and hypertension risk were observed. People with hypertension had a higher salt taste threshold than those with normotension.